Impacts of Land Disputes on Community Development - David Ngwoke Mbazor; Babajide Ojo (TeMA: Journal of Land Use, Mobility and Environment, 2019)
Land disputes as experienced in different parts of Nigeria have strong effect on rural and urban socio-economic development. Land disputes have disastrous and life threatening effects on individuals as well as on groups, communities and even entire nations. In view of this, the study examined the impacts of land disputes on the development of the affected communities. In achieving this, Three hundred and Seventeen (317) questionnaires were retrieved from the residents of the various villages that make up Inyimagu community in Ikwo local government area of Ebonyi state Nigeria, a community that has been ravaged by communal clashes with the adjoining villages including Nsobo community in Obubra local government area of Cross River state over the issue of land ownership. Data were analysed using a simple descriptive statistics. Finding shows that village claim of long time settlements, long-term enmity amongst families among others factors are the major reasons for the incessant land disputes in these communities. This has led to the massive loss of lives and properties both in the past and in the present. Conclusively, it is recommended that that the existing land law system in Nigeria should be comprehensively reviewed to fashion out a best policy such that makes both rural and urban lands to be centrally administered. It is further recommended that affected state governments should as a matter of urgency set up a team of experts such as Estate Surveyors and Valuers, Lawyers, Land Surveyors and Urban and Regional planners to embark on a comprehensive process that would lead to the establishment of land information management system for the states. This, on the long run, would foster an increased understanding of size and boundary of each individual’s hereditament particularly for the lands in dispute.